2023
DOI: 10.1038/s41598-023-35090-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of municipal biowaste derived biostimulant on nitrogen fate in the plant-soil system during lettuce cultivation

Ferdinando Fragalà,
Ivana Puglisi,
Elio Padoan
et al.

Abstract: A main concern of agriculture is to improve plant nutrient efficiency to enhance crop yield and quality, and at the same time to decrease the environmental impact caused by the lixiviation of excess N fertilizer application. The aim of this study was to evaluate the potential use of biopolymers (BPs), obtained by alkaline hydrolysis of the solid anaerobic digestate of municipal biowastes, in order to face up these main concerns of agriculture. The experimental trials involved the application of BPs (at 50 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 57 publications
(69 reference statements)
1
9
2
Order By: Relevance
“…Prior to the present work, the biostimulant effect of BPs applied to soil in solid form was proven in different plant species [ 14 ], including also lettuce [ 7 , 12 ]. However, the foliar spray application of BPs in solution form had never been tested with food crops.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior to the present work, the biostimulant effect of BPs applied to soil in solid form was proven in different plant species [ 14 ], including also lettuce [ 7 , 12 ]. However, the foliar spray application of BPs in solution form had never been tested with food crops.…”
Section: Discussionmentioning
confidence: 99%
“…Fragalà et al [ 7 ] also showed that the application to the soil of solid BPs at a rate of 50 and 150 kg/ha greatly contributed to the ecofriendly sustainability of lettuce production by reducing the consumption of mineral fertilizers during lettuce cultivation, and by the consequent expected mitigation of the environmental impact caused by the mineral nutrient leaching. Although comparing the quantity of solid BPs used by Fragalà et al [ 7 ] and the spray application used in the present study for each plant may result in a very challenging calculation, some speculation suggests that the spray application allows the consumption of BPs to be reduced.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations